Phonological Awareness in Students With Reading Difficulties at Elementary School - Bahrudin Bahrudin; Taboer Mohammad Arif; Rochyadi Endang; Sunardi Sunardi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
Phonological awareness is an essential skill for children to learn to read. Most children with reading difficulties have problems with it. This article was written to describe phonological awareness skills in children with reading difficulties with a descriptive method. There were 31 students with reading difficulties were tested informally. Data analysis was carried out using descriptive techniques and tabulation will define the result of their test. The results showed that there were 25 (81percent) students have problems with phonological awareness. It is indicated almost all students with reading difficulties cannot read with phonological awareness un-mastery. This theme opens up opportunities for further research on phonological awareness of language in primary schools given its importance in teaching reading in schools.